Aclidinium bromide for the treatment of chronic obstructive pulmonary disease. (June 2013) - Cazzola, Mario; Page, Clive P; Matera, Maria Gabriella
<x xml:space="preserve">Abstract</x> Introduction: Although there are some challenges with current therapies, the growing evidence that tiotropium bromide is important in the maintenance treatment of chronic obstructive pulmonary disease (COPD) has led to enthusiastic investigation in search of novel muscarinic antagonists which share some of the beneficial characteristics of tiotropium and perhaps improve upon less desirable ones. Areas covered: <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=Aclidinium bromide&logicalOpe1=OR&field2=articletitle&text2=Aclidinium bromide&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">Aclidinium bromide is a new muscarinic antagonist that has been developed to relieve symptoms in patients with COPD. Preclinical data showed that it has an intriguing pharmacodynamic and pharmacokinetic profile. Aclidinium bromide was initially assessed as a once-daily bronchodilator. Subsequently, it has been evaluated as a twice-daily agent to increase the size of the clinical effect. Pivotal Phase III trials have documented that aclidinium bromide 400 μg twice-daily shows clinically meaningful effects in lung function and other important supportive outcomes, such as health-related quality of life, dyspnea and night-time/early morning symptoms, and is safe. Expert opinion: Aclidinium bromide can to be used as an alternative to tiotropium or a long-acting β2-agonist. It is likely that the device used to deliver aclidinium, Genuair inhaler, a novel, multidose and a breath-actuated dry powder inhaler (DPI), will be important for the possible success of this drug. However, additional Phase III trials to assess advantages over tiotropium bromide and long-acting β2-agonists are required to allow the place of aclidinium bromide to be fully elucidated.